Genome Analysis Revives a Forgotten Hybrid Crop Edo-dokoro in the Genus Dioscorea. (25th July 2022) - Natsume, Satoshi; Sugihara, Yu; Kudoh, Aoi; Oikawa, Kaori; Shimizu, Motoki; Ishikawa, Yuko; Nishihara, Masahiro; Abe, Akira; Innan, Hideki; Terauchi, Ryohei
Abstract: A rhizomatous Dioscorea crop 'Edo-dokoro' was described in old records of Japan, but its botanical identity has not been characterized. We found that Edo-dokoro is still produced by four farmers in Tohoku-machi of the Aomori prefecture, Japan. The rhizomes of Edo-dokoro are a delicacy to the local people and are sold in the markets. Morphological characters of Edo-dokoro suggest its hybrid origin between the two species, Dioscorea tokoro and Dioscorea tenuipes . Genome analysis revealed that Edo-dokoro likely originated by hybridization of a male D. tokoro to a female D. tenuipes, followed by a backcross with a male plant of D. tokoro . Edo-dokoro is a typical minor crop possibly maintained for more than 300 years but now almost forgotten by the public. We hypothesize that there are many such uncharacterized genetic heritages passed over generations by small-scale farmers that await serious scientific investigation for future use and improvement by using modern genomics information.